The conservation status of the Fishing Cat Prionailurus viverrinus Bennett, 1833 (Carnivora: Felidae) In Koshi Tappu Wildlife Reserve, Nepal - Iain Rothie Taylor (Journal of Threatened Taxa, 2016)
The status of the Fishing Cat Prionailurus viverrinus in Koshi Tappu Wildlife Reserve, Nepal was assessed by camera trapping and pugmark searches from 2011 to 2014.  The reserve is a highly dynamic and unstable snow-fed braided river system with many anabranches and islands.  Evidence of Fishing Cats was found throughout most of the reserve.  They were probably more abundant on the eastern side, among the islands of the main river channel, and in the adjacent buffer zone where there was a chain of fishponds and marsh areas fed by seepage from the main river channel.  Evidence of Fishing Cats was found up to 6km north of the reserve on the Koshi River but not beyond this.  The population is probably small and may be isolated but given the endangered status of the species, is significant.  The main likely threats identified are wetland and riparian habitat deterioration caused by over exploitation and illegal grazing by villagers, overfishing of wetlands and rivers within the reserve, and direct persecution arising from perceived conflicts with fish farming and poultry husbandry.  Required conservation actions are discussed.